PENGARUH TENAGA KERJAASING TERHADAP PERTUMBUHANEKONOMIDAN KESEMPATAN KERJA: Suatu Tinjauan Literatur - Nasri Bachtiar; Rahmi Fahmi (Jurnal Kependudukan Indonesia, 2011)
Although there were many researchers have studied about the contributions of influx of foreign workers toward the economic growth, job opportunities, and the wage rate in certain country, there were still some debatable results on these topics. In one hand, some researchers suggested that the influx of foreign workers had improved the increasing of output growth, job opportunities and wage rate. While on the other hand some researchers stated that the influx of foreign workers could cause the slowdown of these aspects. Some reasons to the last arguments were the foreign workers could bring the opposite impacts which were prevented the increasing of the economic growth, eliminated job opportunities and the level of wage fqr the local workers since the foreign workers had lower education and skills than local workers. In these cases, the researchers had arguments that the foreign workers were seen as substitute in production process On the other cases, if the foreign workers had better education and skills than lokal workers, they were seen as complementary in production process.Keywords: foreign worker, economic growth, employment and weges